Effect of Antibiotic Stewardship Prior to Outpatient Cystoscopy; Prospective longitudinal study - Khan, Ubaid Ullah; Imran, Mishal; Ullah , Azmat; Nawaz, Muhammad; Khan, Jibran Jabbar; Haider, Syed Yazdan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To determine the effect of antibiotic stewardship prior to outpatient cystoscopy. Study Design: Prospective longitudinal study. Place and Duration of Study: Armed Forces Institute of Urology, Rawalpindi Pakistan, from Aug 2022 to Feb 2023. Methodology: 240 consecutive patients from OPD who had a cystoscopy indication were enrolled. After submitting a voided urine sample for culture, every patient underwent cystoscopy. Bacteriuria was considered significant when the number of colony-forming units per millilitre was greater than 104 for a single organism. Known risk factors for UTIs were used to stratify the patients. Patients did not take any antibiotics in the hours leading up to or following the flexible cystoscopy procedure. For thirty days, they were monitored for the development of a febrile UTI. Having a temperature greater than 38 degrees Celsius along with dysuria or having antibiotics prescribed by a doctor for urinary tract infections were criteria for a febrile UTI. Results: Out of 240 patients 36(18.95%) had nitrate, 29(15.26%) patients had Esterase, 55(28.9%) patients had WBC’s on urine microscopy and 33(17.37%) patients had Positive urine culture. At the p-value of 0.049, the only significant factors in the development of a febrile UTI were older age (40–60 years) and bacteriuria. The odds ratio was 0.99 and the confidence interval was .. Conclusion: There appears to be no need for antibiotic medication prior to outpatient flexible cystoscopy in patients who do not exhibit any....